Express forecast of the radiation stress to the population from NPP gazoaerozol emissions NPP - L. I. Grygorieva; Ya. A. Tomilin; K. V. Grygoriev (Ядерна фізика та енергетика)
Express method of forecast evaluation values of dose load to the population from the territories under the simultaneous influence of radionuclide pollutants natural and artificial origin was proposed. Based on the results of radioecological research in the areas exposed to aerosol emissions of South Ukrainian and Zaporizhzhya NPPs the values and the average human life expectancy for normalized values radiation dose aerosol emissions from nuclear power plants that can facilitate the work of dosimetric monitoring of areas near nuclear power plants were calculated.